Impedance properties and microwave magnetic field dependence of surface resistance of YBaCuO - Velichko, A.V.; Cherpak, N.T.; Izhyk, E.V.; Kirichenko, A.Ya.; Chukanova, I.N.; Zagoskin, V.T. (Физика низких температур, 1996)
The microwave magnetic field IIw dependence of the surface resistance Rs for a YBa₂Cu₃O-δ ceramic and thin film has been studied in 8 mm wave band. It is shown that for the film one of mechanisms consistent with the obtained dependence Rs(Hw) may be microwave-induced flux motion. For the ceramic specimen, the above dependence is in agreement with the model of Sridhar for the nonlinear high-frequency response of a planer superconductor in a current-induced critical state and with Gurevich's theory of the nonlinear dynamics of vortices in high-Jc overdamped Josephson contacts. An approach was applied which allows us to perform measurements without preliminary patterning of the samples.